A study of blood pressure levels and other factors that contribute to a good pregnancy outcome - Karanasiou, Eleni Apostolos; Karvana, Thaleia; Rizothanasi, Konstantina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of this study was to investigate the awareness of blood pressure before and during pregnancy by pregnant women as well as the factors of pathological increase and if woman is going to adapt to the new situation changing their lifestyle and food habits during pregnancy . Methods: The study was conducted on 318 pregnant women to assess their knowledge and attitude about pregnancy and the development of high-risk pathology who had visited the Public Obstetric Hospital of Athens “Elena Venizelou”, from December 2019 to August 2020. Then were given a pre-designed structured questionnaire on socio-demographic, variable knowledge and attitude about health and pregnancy. Results: According to the study it was found that a proportion watching their diet (61%), limiting smoking (29% smoker, 12% of them smokes minimum), but a large number of them were unaware of preeclampsia (46%) and especially whether an increase in blood pressure occurs in preeclampsia (45%), leg edema (56%) and albuminuria (74%), while 77% of them ignore what is albuminuria and this is directly linked to the level of education, age and nationality. Conclusions: The study concludes that a large number of the sample ignores the complications of pregnancy and the development of these predisposing factors. The main disadvantage of this study is that there was not a random sample of people asked. Thus, in the future it is proposed that a similar survey should be conducted in various nursing institutions.